2019
DOI: 10.1016/j.surfcoat.2019.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for the production of SiC micro and nanopatterns

Abstract: HIGHLIGHTS A novel method was demonstrated for the production of SiC micro and nanopatterns  Patterning and SiC compound formation happened in one step at room temperature  The SiC formation was proved by AES depth profiling  Two different patterns were presented  The method can be considered as a possibility to fabricate SERS substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Harbsmeier et al have shown that ion bombardment can induce solid state reaction in Si&C mixture [17]. Racz et al showed that SiC nano-layer can be produced by IBM at room temperature [18,19].…”
Section: Introductionmentioning
confidence: 99%